THER-28. A CK1α ACTIVATOR PENETRATES THE BRAIN, AND SHOWS EFFICACY AGAINST DRUG-RESISTANT METASTATIC MEDULLOBLASTOMA. (23rd April 2019) - Rodriguez, Jezabel; Li, Bin; Long, Jun; Shen, Chen; Yang, Fan; Orthon, Darren; Collins, Sara; Kasahara, Noriyuki; Ayad, Nagi; McCrea, Heather; Roussel, Martine; Weiss, William; et al.
Abstract: Although most children with medulloblastoma (MB) are cured of their disease, SONIC HEDGEHOG (SHH) subgroup MB driven by TRP53 mutations is essentially lethal. Casein Kinase 1α (CK1α) phosphorylates and destabilizes GLI transcription factors, thereby inhibiting the key effectors of SHH signaling. We therefore tested a second-generation CK1α activator against, TRP53 mutant, MYCN amplified MB. Our novel CK1α activator inhibited SHH activity in vitro, acting downstream of the vismodegib target SMOOTHENED (SMO), and reduced the viability of sphere cultures derived from SHH MB. SSTC3 accumulated in the brain, inhibited growth of SHH MB tumors, and blocked metastases in a genetically-engineered vismodegib-resistant mouse model of SHH MB. Importantly, SSTC3 attenuated growth and metastasis of orthotopic patient-derived TRP53 mutant, MYCN amplified, SHH subgroup MB xenografts, increasing overall survival. Thus, a CK1α agonist penetrates into the brain, and shows efficacy against metastatic TRP53 mutant MB, which are resistant to existing therapies including the SMO inhibitors currently being evaluated clinically.